Cha rā toʻ ʼA rhaṅʻ Seṭṭhila e* bhava phracʻ cañʻ nhaṅʻʹ kambhāʹ buddhasāsanā pru mhatʻ tamʻʺ - Ñānika, ʼA rhaṅʻ (Pyoʻ bhvayʻ Ūʺ Taṅʻ ʼOṅʻ, 1990)
Life and work of Ashin Thittila, b. 1896, Burmese Buddhist priest.